Diffraction-based Residual Stress Mapping of a Stress Frame of Gray Iron via Vibratory Stress Relief Method - Chen, Shi-Wei; Huang, E-Wen; Chiu, Sung-Mao; Reid, Mark; Wu, Cheng-Yen; Paradowska, Anna M.; Lam, Tu-Ngoc; Wu, Yu-Hao; Lee, Soo Yeol; Lu, Shao-Chien; Chen, Shin-An; Lin, Yan-Gu; et al. (Frontiers in Materials, 2022)
The role of residual stress is critical, especially for machine tools demanding an accuracy below 1 µm. Because when minor stresses are subjected to a tiny area, the applied force can cause devastating distortions on the precision components at this length scale. In this research, we systematically investigated the residual stress in a stress frame of grey iron, used in machine tools, using synchrotron X-ray and neutron sources. Through the combination of these techniques, the residual stresses on the surface, inside the bulk, and in average were presented. Comprehensive analysis results shed light on the vibratory stress relief technique which reduced the residual stresses and stabilized them even materials undergoing cycling heating. Although only tensile stresses and not compressive stresses are effectively reduced, this technique is useful in improving the mechanical stability of materials in machine tools.